Системний підхід при економіко-математичному моделюванні економічної безпеки будівельного підприємства - Молодід, О. О. (Ways to Improve Construction Efficiency, 2012)
The complextechno-econometric relationshipsto determine therevenueandcostof the value offixed assets,current assetsandthe cost of labor, whichallows to predict thelevelof economic securityof the constructioncompany.The resultingcomplextestedforadequacybythe coefficient ofdetermination(R2)and F-Fisher criterion.